Ciliary body size in chronic angle-closure glaucoma - Jonas, Jost B.; Jonas, Rahul A.; Jonas, Shefali B.; Panda-Jonas, Songhomitra (Scientific reports, 2023)
To examine the size of the ciliary body stroma (CBS) in dependence of the morphology of the anterior chamber angle in enucleated human eyes, we histomorphometrically examined human enucleated eyes. The study included 107 eyes (with a mean axial length of 25.1 ± 2.8 mm (range 21.0-36.0 mm). The anterior chamber angle was open in 68 eyes and it was closed and endothelialized in 39 eyes. The maximal CBS width (541 ± 210 µm versus 59 ± 179 µm; P < 0.001) and the minimal CBS width (214 ± 107 µm versus 17 ± 55 µm; P < 0.001) and maximal ciliary muscle height (593 ± 557 µm versus 293 ± 111 µm; P = 0.001) were significantly smaller in the angle-closure group than in the open-angle group. Maximal CBS width increased with presence of an open anterior chamber angle (beta: 0.82; B: 517; 95% CI 435, 599; P < 0.001) and longer axial length (beta: 0.17; B: 18.2; 95% CI 4.2, 32.2; P = 0.01). Minimal CBS width increased with the presence of an open anterior chamber angle (beta: 0.48; B: 131; 95% CI 80.4, 181; P < 0.001) and a larger maximal ciliary muscle height (beta: 0.33; B: 0.28; 95% CI 0.12, 0.44; P = 0.001). Maximal ciliary muscle height correlated with the maximal CBS height (beta: 0.35; B: 0.53; 95% CI 0.25, 0.81; P < 0.001). The findings suggest that the CBS size is markedly smaller in eyes with a chronically closed endothelialized anterior chamber angle than in eyes with open angles. The tightening of the angle in eyes with angle-closure may prevent the access of aqueous humor not only to the trabecular meshwork but also to the ciliary body and may reduce the uveoscleral or uveovortex outflow pathway.